Reduction of thermal emission background in high temperature microheaters. (5th April 2016) - Armstrong, Philip R; Mah, Merlin L; Olson, Kyle D; Taylor, Lucas N; Talghader, Joseph J
Abstract: High temperature microheaters have been designed and constructed to reduce the background thermal emission radiation produced by the heater. Such heaters allow one to probe luminescence with very low numbers of photons where the background emission would overwhelm the desired signal. Two methods to reduce background emission are described: one with low emission materials and the other with interference coating design. The first uses platforms composed of material that is transparent to mid-infrared light and therefore of low emissivity. Heating elements are embedded in the periphery of the heater. The transparent platform is composed of aluminum oxide, which is largely transparent for wavelengths less than about 8 μ m. In the luminescent microscopy used to test the heater, an optical aperture blocks emission from the heating coils while passing light from the heated objects on the transparent center of the microheater. The amount of infrared light transmitted through the aperture was reduced by 90% as the aperture was moved from the highly emissive heater coils at 450 °C to the largely transparent center at the same temperature. The second method uses microheaters with integrated multilayer interference structures designed to limit background emission in the spectral range of the low-light luminescence object being measured. These heaters were composed of aluminum oxide, titanium dioxide, and platinum and were operated over a large range of temperatures, from 50 °C to 600 °C. At 600 °C, they showed a background photon emission only 1/800 that of a comparison heater without the multilayer interference structure. In this structure, the radiation background was sufficiently reduced to easily monitor weak thermoluminescent emission from CaSO4 :Ce, Tb microparticles.